Insulin signal decrease in muscle but not in the liver of castrated male rats from chronic exposure to fluoride - Chiba, Fernando Yamamoto [UNESP]; Colombo, Natália Helena [UNESP]; Shirakashi, Daisy Jaqueline [UNESP]; Gomes, Wendrew Douglas De Souza [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Silva, Cristina Antoniali [UNESP]; Sumida, Doris Hissako [UNESP] (My University, 2010)
With half the animals as controls without fluoride (F) in their drinking water, 16 of 32 seven-week-old castrated male Wistar rats were administered NaF in their drinking water and F contained in food pellets (estimated total F intake: 4.0 mg F/kg bw/day). After 42 days, determinations were made of the insulin receptor substrate (pp185-IRS-1/IRS/2), tyrosine phosphorylation status, and the extent of glycemia and insulinemia. This chronic treatment with F promoted: 1) decrease in the pp185 tyrosine phosphorylation status in the muscle tissue but not in the liver; 2) increase in the plasma F level; 3) no alteration in glycemia and insulinemia; 4) an increase in insulin resistance. Copyright © 2010 The International Society for Fluoride Research Inc.
Keywords: Fluoride; Insulin receptor substrate; Insulin sensitivity; Insulin signal; Rats and insulin